Relationship Between Pre Operation Risk Factor Profiles With Clinical Outcomes In Post Isolated CABG Patients Treated In ICU - Daondy Friarsa Soeharto; Rita Zahara; Bagus Herlambang; Bambang Widyantoro; Sugisman Sugisman (The Indonesian Heart Association, 2026)
Background: Atherosclerotic Cardiovascular Disease (ASCVD) causes around 31% death all over the world. This disease can be managed with Coronary Artery Bypass Graft (CABG). Although its success ratio continues to increase, patients tend to have more complex conditions, which complicate the results. Methods: This retrospective cohort study was conducted with samples consisting of ≥18 years old patients who underwent isolated CABG between January 2017 and June 2022 and were admitted to the Intensive Care Unit (ICU) afterward. Clinical outcomes measured were prolonged ICU and intrahospital mortality. A 77-hour post-procedural ICU treatment period is considered the standard of care. Result: A total of 2611 patients were included. The mean age was 59 years. Geriatric, overweight, obesity, kidney failure, Heart Failure with reduced Ejection Fraction (HFrEF), Cardiogenic Shock, Left Main Disease (LMD), and Pre Incision Intra-Aortic Balloon Pump (IABP) are associated with prolonged ICU care; while female gender, Family history of ASCVD, Diabetes, Hypertension, Acute Coronary Syndrome (ACS), Stroke, and history of cardiac surgery are associated with higher mortality. The lengthening of ICU care is also associated with higher mortality (OR 4.02; p<0.00). According to multivariate analysis, the factors associated with prolonged ICU are geriatric, obesity, kidney failure, stroke, HFrEF, Cardiogenic shock, very poor Ejection Fraction (EF), urgent procedure and pre incision IABP, meanwhile factors associated with mortality are female, diabetes, stroke, history of ACS<24H, poor and very poor EF, History of Cardiac Surgery, and prolonged ICU itself. Conclusion: In Indonesian isolated CABG patients, prolonged ICU stay and increased mortality are independently driven by specific demographic, comorbid, and clinical factors, necessitating targeted preoperative risk assessment to optimize outcomes.